Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Adaptive Software Development: A Collaborative Approach to Managing Complex Systems - Highsmith, Jim (Dorset House Publishing, 2000)
In today's turbulent e-business world, software project teams that survive and thrive won't be those that continue their traditions of optimization, efficiency, and control, but those that exhibit adaptability, speed, and collaboration. Adaptive Software Development is targeted at software teams where competition creates extreme pressure on the delivery process. Four goals of the book are * to support an adaptive culture in which change and uncertainty are assumed to be the natural state * to introduce frameworks to guide the iterative process of managing change * to institute collaboration, the interaction of people on interpersonal, cultural, and structural levels * to add rigor and discipline to the RAD approach, making it scalable to the uncertainty and complexity of real-world undertakings. This innovative text, grounded in the science of complex adaptive systems theory, offers a practical, realistic approach to managing the high-speed, high-change projects characteristic of our highly uncertain economy.

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Agile Software Development: Adaptive Systems Principles and Best Practices - Meso, Peter; Jain, Radhika (Information Systems Management, 2006)
Today's environments of increasing business change require software development methodologies that are more adaptable. This article examines how complex adaptive systems (CAS) theory can be used to increase our understanding of how agile software development practices can be used to develop this capability. A mapping of agile practices to CAS principles and three dimensions (product, process, and people) results in several recommendations for “best practices” in systems development.
Keywords: IMPORTANT

Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments―now updated with new techniques for larger projectsToday, the pace of project management moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromising value, quality, or business discipline. In Agile Project Management, Second Edition, renowned agile pioneer Jim Highsmith thoroughly updates his classic guide to APM, extending and refining it to support even the largest projects and organizations.  Writing for project leaders, managers, and executives at all levels, Highsmith integrates the best project management, product management, and software development practices into an overall framework designed to support unprecedented speed and mobility. The many topics added in this new edition include incorporating agile values, scaling agile projects, release planning, portfolio governance, and enhancing organizational agility. Project and business leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, quality, and constraints. This edition’s coverage includes: Understanding the agile revolution’s impact on product development Recognizing when agile methods will work in project management, and when they won’t Setting realistic business objectives for Agile Project Management Promoting agile values and principles across the organizationUtilizing a proven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five stages of the agile project: Envision, Speculate, Explore, Adapt, and CloseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for executives and management  The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Navigating adaptive approaches for development programmes - Pett, Jamie (Working Paper, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

Developing an effective adaptive monitoring network to support integrated coastal management in a multiuser nature reserve - Vugteveen, Pim; van Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support Integrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling actions essential to accomplish and sustain monitoring excellence to support ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online data portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioeconomic data and links research-driven and policy-driven monitoring for system analysis using indicators of pressures, state, benefits, and responses. The approach and concepts we elaborated are transferable to other coastal regions to accomplish ICM in complex social-ecological systems in which scientists, multisectoral stakeholders, resource managers, and governmental representatives seek to balance long-term ecological, economic, and social objectives within natural limits.
Keywords: IMPORTANT

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.

Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Publishing, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

The Dynamics of Team Learning: Harmony and Rhythm in Teamwork Arrangements for Innovation - Harvey, Jean-François; Cromwell, Johnathan R.; Johnson, Kevin J.; Edmondson, Amy C. (Administrative Science Quarterly, 2023)
Innovation teams must navigate inherent tensions between different learning activities to produce high levels of performance. Yet, we know little about how teams combine these activities—notably reflexive, experimental, vicarious, and contextual learning—most effectively over time. In this article, we integrate research on teamwork episodes with insights from music theory to develop a new theoretical perspective on team dynamics, which explains how team activities can produce harmony, dissonance, or rhythm in teamwork arrangements that lead to either positive or negative effects on overall performance. We first tested our theory in a field study using longitudinal data from 102 innovation teams at a Fortune Global 500 company; then, we replicated and elaborated our theory in a study of 61 MBA project teams at an elite North American university. Results show that some learning activities can occur within the same teamwork episode to have harmonious positive effects on team performance, while other activities combine to have dissonant negative effects when occurring in the same episode. We argue that dissonant activities must be spread across teamwork episodes to help teams achieve a positive rhythm of team learning over time. Our findings contribute to theory on team dynamics, team learning, and ambidexterity.

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (2019 CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Resilience Thinking: Sustaining Ecosystems and People in a Changing World - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, ecosystems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: more control, more intensification, and greater efficiency. "Resilience thinking" offers a different way of understanding the world and a new approach to managing resources. It embraces human and natural systems as complex entities continually adapting through cycles of change and seeks to understand the qualities of a system that must be maintained or enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a constructive alternative that opens up options rather than closing them down. In "Resilience Thinking", scientist Brian Walker and science writer David Salt present an accessible introduction to the emerging paradigm of resilience. The book arose out of appeals from colleagues in science and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices. Rather than complicated theory, the book offers a conceptual overview along with five case studies of resilience thinking in the real world. It is an engaging and important work for anyone interested in managing risk in a complex world.

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)